¿Modernización o hegemonía? : asesoría económica norteamericana a América Latina - Fermandois, Joaquín (Estudios Internacionales, 1995)
Reseña del libro: Money doctors, foreign debt, and ecomic reforms in Latin America from the 1890s to the present, by Paul W, Drake Wilmington, Delaware: SR Books, Jaguar Books on Latin America, 3, 1994